IMPLEMENTATION OF PROJECT-BASED LEARNING FOR NATURALISTIC INTELLIGENCE AND THE INSTILLATION OF MORAL RELIGIOUS VALUES IN GROUP B - Regina Putri, Adinda Anastasya; Tine, Nurhayati; Ardini, Pupung Puspa (Jambura Journal Civic Education, 2025)
study seeks to elucidate the implementation process of project-basedlearning aimed at enhancing naturalistic intelligence in Group B at MekarHulawa State Kindergarten, located in Telaga District, Gorontalo Regency.The research objectives include analyzing and evaluating the effectivenessof project-based learning in fostering naturalistic intelligence within thiscohort, as well as examining the school's approach to implementing suchpedagogical strategies. Employing a qualitative descriptive methodology,the study involved grade B teachers as subjects, with the principal and thegrade B assistant teacher serving as research informants. Data collectionwas conducted through observation, interviews, and documentation, withdata validity ensured via source and technique triangulation. The dataanalysis process encompassed (1) data condensation, (2) datapresentation, and (3) conclusion drawing. The findings reveal that theimplementation of project-based learning for naturalistic intelligence inGroup B at Mekar Hulawa State Kindergarten has been successful. Theactivities encompassed topic introduction, concept map development,learning activities, and evaluation. Children were actively engaged as thefocal point of the learning process. Observable outcomes include theenhancement of naturalistic intelligence, increased willingness to exploreand interact with the natural environment, improved ability to articulateopinions, enhanced collaboration with peers and teachers, and thedevelopment of critical thinking and creativity.